The Factors Associated with Outcomes in Surgically Managed Ruptured Cerebral Aneurysm - Chee, Lai Chuang (Malays J Med Sci, 2018)
BACKGROUND: Ruptured cerebral aneurysm is a life-threatening condition that requires urgent medical attention. In Malaysia, a prospective study by the Umum Sarawak Hospital, Neurosurgical Center, in the year 2000–2002 revealed an average of two cases of intracranial aneurysms per month with an operative mortality of 20% and management mortality of 25%. Failure to diagnose, delay in admission to a neurosurgical centre, and lack of facilities could have led to the poor surgical outcome in these patients. The purpose of this study is to identify the factors that significantly predict the outcome of patients undergoing a surgical clipping of ruptured aneurysm in the local population. MATERIAL AND METHOD: A single center retrospective study with a review of medical records was performed involving 105 patients, who were surgically treated for ruptured intracranial aneurysms in the Sultanah Aminah Hospital, in Johor Bahru, from July 2011 to January 2016. Information collected was the patient demographic data, Glasgow Coma Scale (GCS) prior to surgery, World Federation of Neurosurgical Societies Scale (WFNS), subarachnoid hemorrhage (SAH) grading system, and timing between SAH ictus and surgery. A good clinical grade was defined as WFNS grade I–III, whereas, WFNS grades IV and V were considered to be poor grades. The outcomes at discharge and six months post surgery were assessed using the modified Rankin’s Scale (mRS). The mRS scores of 0 to 2 were grouped into the “favourable” category and mRS scores of 3 to 6 were grouped into the “unfavourable” category. Only cases of proven ruptured aneurysmal SAH involving anterior circulation that underwent surgical clipping were included in the study. The data collected was analysed using the Statistical Package for Social Sciences (SPSS). Univariate and multivariate analyses were performed and a P-value of < 0.05 was considered to be statistically significant. RESULT: A total of 105 patients were included. The group was comprised of 42.9% male and 57.1% female patients. The mean GCS of the patients subjected to surgical clipping was 13, with the majority falling into the good clinical grade (78.1%). The mean timing of the surgery after SAH was 5.3 days and this was further categorised into early (day one to day three, 45.3%), intermediate (day four to day ten, 56.2%), and late (after day ten, 9.5%). The total favourable outcome achieved at discharge was 59.0% as compared to 41.0% of the unfavourable outcome, with an overall mortality rate of 10.5%. At the six-month post surgery review (n = 94), the patients with a favourable outcome constituted 71.3% as compared to 28.7% with an unfavourable outcome. The mortality, six months post surgery was 3.2%. On a univariate analysis of early surgical clipping, patients with a better GCS and good clinical grade had a significantly better outcome at discharge. Based on the univariate study, six months post surgery, the timing of the surgery and the clinical grade remained significant predictors of the outcome. On the basis of the multivariate analysis, male patients of younger age, with a good clinical grade, were associated with favourable outcomes, both at discharge and six months post surgery. CONCLUSION: In this study, we concluded that younger male patients with a good clinical grade were associated with a favourable outcome both at discharge and six months post surgery. We did not find the timing of the surgery, size of the aneurysm or duration of surgery to be associated with a patient’s surgical outcome. Increasing age was not associated with the surgical outcome in a longer term of patient’s follow up.